Combination of SRME And WEMR Seismic Noise Demultiple With CRS Stack Method - Zein, Emir Dzakwan Kamal; Rasimeng , Syamsurijal; Wijaksono, Egie (Universitas Negeri Surabaya, 2024)
Marine seismic data recordings consist of signals and various types of noise which can reduce the quality of the resulting data processing model. This research purpose to increase the signal to noise ratio of a 2D seismic cross-section using the demultiple and stacking methods. This research method applying the Common Reflection Surface (CRS) stack method with a combination of two seismic noise demultiple methods, namely Surface Related Multiple Elimination (SRME) and Wave Equation Multiple Rejection (WEMR) using ProMAX software. The CRS stack results has been proven to be able to eliminate random noise, increase amplitude, and clarify existing reflector patterns. The radon analysis feature can also assist the data quality control process related to the presence of multiple noise indications. The SRME and WEMR demultiple results can predict different multiple models so that later they can be subtracted from the main data. The multiple SRME prediction results is characterized by shape, size and wavelet pattern, whose overall trace appearance tends to be similar and not too complex. The multiple WEMR prediction results has characteristics of shape, size and wavelet pattern whose overall trace is almost similar and slightly more complex. The combination of the CRS, SRME, and WEMR stack methods is concluded to be able to reduce the presence of noise, so that the main reflector pattern is easier to identify as the actual subsurface layer. However, there are still indications of the existence of multiple residues that have not been completely reduced. Therefore, further research is needed, especially in combining the CRS stack, F-K filter, Radon filter, SRME, and WEMR methods.